2024
DOI: 10.1186/s12872-024-03711-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and bioinformatic prediction for profile of mRNA bound to circular RNA BTBD7_hsa_circ_0000563 in coronary artery disease

Ning Guo,
Hanxiao Zhou,
Qian Zhang
et al.

Abstract: Background As a novel circRNA, BTBD7_hsa_circ_0000563 has not been fully investigated in coronary artery disease (CAD). Our aim is to reveal the possible functional role and regulatory pathway of BTBD7_hsa_circ_0000563 in CAD via exploring genes combined with BTBD7_hsa_circ_0000563. Methods A total of 45 peripheral blood mononuclear cell (PBMC) samples of CAD patients were enrolled. The ChIRP-RNAseq assay was performed to directly explore genes bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that, while knockout of RIP3 in an ApoE −/− mouse model had minimal impact on early-stage AS, it significantly alleviated late-stage atherosclerotic lesions, revealing the connection between necroptosis and plaque stability ( 77 ). Furthermore, elevated plasma levels of RIP3 are positively associated with the severity of coronary artery disease, suggesting its potential as an indicator for assessing the severity of coronary artery disease ( 78 ).…”
Section: Necroptosis and Its Relationship With Cvdsmentioning
confidence: 99%
“…Studies have shown that, while knockout of RIP3 in an ApoE −/− mouse model had minimal impact on early-stage AS, it significantly alleviated late-stage atherosclerotic lesions, revealing the connection between necroptosis and plaque stability ( 77 ). Furthermore, elevated plasma levels of RIP3 are positively associated with the severity of coronary artery disease, suggesting its potential as an indicator for assessing the severity of coronary artery disease ( 78 ).…”
Section: Necroptosis and Its Relationship With Cvdsmentioning
confidence: 99%